2012
DOI: 10.1210/jc.2012-1589
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue and Its Relationship to Bone Structure in Pediatric Patients

Abstract: The volume of BAT is positively associated with the amount of bone and the cross-sectional size of the femur in children and adolescents. This relation between BAT and bone structure could, at least in part, be mediated by muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 24 publications
(23 reference statements)
3
65
0
2
Order By: Relevance
“…The authors also found a positive correlation between BAT volume and thigh muscle CSA. This is in line with the results of a previous study showing that children and teenagers with detectable BAT, as determined by 18 F-FDG-PET/CT, have a significantly greater muscle volume than individuals with no detectable BAT. 41 In addition to the human studies mentioned above, a couple of animal studies have recently evaluated the effects of BAT on bone structure.…”
Section: The Connection Between Bat and Bonesupporting
confidence: 92%
See 3 more Smart Citations
“…The authors also found a positive correlation between BAT volume and thigh muscle CSA. This is in line with the results of a previous study showing that children and teenagers with detectable BAT, as determined by 18 F-FDG-PET/CT, have a significantly greater muscle volume than individuals with no detectable BAT. 41 In addition to the human studies mentioned above, a couple of animal studies have recently evaluated the effects of BAT on bone structure.…”
Section: The Connection Between Bat and Bonesupporting
confidence: 92%
“…Lee et al 17 found a similar positive correlation between BAT volume and BMD in a group of healthy women, but not in men, suggesting the possibility of a gender-specific connection between BAT and bone. However, such gender-specific connection was not found in a cross-sectional study by Ponrartana et al 18 that showed a significant correlation between BAT volume and femoral cortical bone area and cross-sectional area (CSA) in children and teenagers regardless of sex. Notably, the authors of the study did not exclude the possibility that the association between BAT and bone could, at least in part, be mediated by skeletal muscle, as the predictive power of the model increased by adding skeletal muscle as an independent variable while significantly decreasing the contribution of BAT.…”
Section: The Connection Between Bat and Bonementioning
confidence: 90%
See 2 more Smart Citations
“…On this basis we applied an SUV threshold for quantification of BAT volume/activity of ≥1.0 g/ml; while this might be considered low, it is consistent with previous studies reporting increased activity in BAT in this region [30,36,37]. Moreover, the preliminary analysis described above established that there was no overlap with WAT [36,37]. For this analysis we are also confident that this method did not include skeletal muscle, first because of the radiodensity criteria (−180 to −10 Hounsfield units) and second because skeletal muscle SUVmax was ≤0.8 g/ml.…”
Section: Dose Rationalesupporting
confidence: 77%